2014
DOI: 10.15448/1984-7289.2014.2.17155
|View full text |Cite
|
Sign up to set email alerts
|

Memória de idosos: As narrativas em diferentes espaços de interação social

Abstract: Memória de idosos As narrativas em diferentes espaços de interação social Elderly memories Narratives in different spaces of social interaction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research held with young Computer Science students and elderly people proved the effectiveness of sharing experiences between generations. Results of this research showed that the elders were capable of recognizing the value of their own history, and young people, responsible for transmitting some computing knowledge, could review their negative perceptions on older people, besides perceiving how helpful they could be to this ageing population, helping them use the new technologies 16 .…”
Section: Discussionmentioning
confidence: 94%
“…Research held with young Computer Science students and elderly people proved the effectiveness of sharing experiences between generations. Results of this research showed that the elders were capable of recognizing the value of their own history, and young people, responsible for transmitting some computing knowledge, could review their negative perceptions on older people, besides perceiving how helpful they could be to this ageing population, helping them use the new technologies 16 .…”
Section: Discussionmentioning
confidence: 94%